Effect of legume cropping and organic matter accumulation on the infiltration rate and structural stability of a granite soil under a simulated tropical environment - Yaacob, Othman; Blair, Graeme J. (Springer, 1981)
An experiment was conducted under a simulated tropical environment to examine the effect of legume cropping on the infiltration rate and aggregate stability of a sandy granite soil. The stability of aggregates >2 mm increased from 47.3% in soil on which one siratro crop had been grown to 61.6% where six crops had been grown. In a soil on which soybeans had been grown this increase was from 39.4 to 77.1%. Infiltration rate (IR) was measured over a 30 min. period using a constant 2.5 cm head. IR in the 0 to 5 min. time period was related to soil total nitrogen by the relationship y=158.5x−0.738, (R=0.87**) where y=infiltration rate and x=soil total N(%). Beyond 5 minutes IR was determined by the sub-soil permeability. These results demonstrate the beneficial effects of legume cropping on infiltration rate and structural stability and the difficulty of improving soil water relations in soils with impermeable sub-soils.